Sowing dates and capitulum characteristics of sunflower cultivars - Solasi, Angel Dario; Mundstock, Claudio Mario (Pesquisa Agropecuaria Brasileira, 1992)
The effects of three sowing dates (July 28, September 3 and October 14, 1986) and three sunflower cultivars (Contisol 112, Contisol 711 and Issanka) on capitulum characteristics were evaluated at Eldorado do Sul, RS, Brazil, during the 1986/87 growing season. Flower number per capitulum was similar between sowing dates but sterile/abortive flowers (in central region) were more abundant at July sowing date, for two cultivars tested, which affected achene number and also grain yield. Achene weight varied according lo planting date and cultivar. Yields were determined by variations of both achene number and achene weight.